AlkAniline‐Seq: Profiling of m7G and m3C RNA Modifications at Single Nucleotide Resolution. (16th November 2018) - Marchand, Virginie; Ayadi, Lilia; Ernst, Felix G. M.; Hertler, Jasmin; Bourguignon‐Igel, Valérie; Galvanin, Adeline; Kotter, Annika; Helm, Mark; Lafontaine, Denis L. J.; Motorin, Yuri
Abstract: RNA modifications play essential roles in gene expression regulation. Only seven out of >150 known RNA modifications are detectable transcriptome‐wide by deep sequencing. Here we describe a new principle of RNAseq library preparation, which relies on a chemistry based positive enrichment of reads in the resulting libraries, and therefore leads to unprecedented signal‐to‐noise ratios. The proposed approach eschews conventional RNA sequencing chemistry and rather exploits the generation of abasic sites and subsequent aniline cleavage. The newly generated 5′‐phosphates are used as unique entry for ligation of an adapter in library preparation. This positive selection, embodied in the AlkAniline‐Seq, enables a deep sequencing‐based technology for the simultaneous detection of 7‐methylguanosine (m 7 G) and 3‐methylcytidine (m 3 C) in RNA at single nucleotide resolution. As a proof‐of‐concept, we used AlkAniline‐Seq to comprehensively validate known m 7 G and m 3 C sites in bacterial, yeast, and human cytoplasmic and mitochondrial tRNAs and rRNAs, as well as for identifying previously unmapped positions. Abstract : „Deep Sequencing" wurde genutzt, um ein neues Konzept für den Aufbau von Bibliotheken zum Nachweis spezifischer DNA‐Modifikationen zu entwickeln. Modifizierte RNA wird alkalischer Hydrolyse ausgesetzt, dephosphoryliert und an abasischen Stellen mit Anilin gespalten. Die resultierenden 5′‐Phosphate werden für die spezifische Ligation von Sequenzierungsadaptern genutzt. Die Methode kann für den empfindlichen Nachweis von m 7 G, m 3 C und (D)‐Resten in RNAs verwendet werden.